2012
DOI: 10.2527/jas.2011-5077
|View full text |Cite
|
Sign up to set email alerts
|

Genetic parameters for carnitine, creatine, creatinine, carnosine, and anserine concentration in longissimus muscle and their association with palatability traits in Angus cattle1

Abstract: The objective of this study was to estimate genetic parameters for carnitine, creatine, creatinine, carnosine, and anserine concentration in LM and to evaluate their associations with Warner-Bratzler shear force (WBSF) and beef palatability traits. Longissimus muscle samples from 2,285 Angus cattle were obtained and fabricated into steaks for analysis of carnitine, creatine, creatinine, carnosine, anserine, and other nutrients, and for trained sensory panel and WBSF assessments. Restricted maximum likelihood p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
30
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 46 publications
5
30
0
Order By: Relevance
“…Mateescu et al. () reported heritabilities of anserine and carnosine in Angus cattle similar to those reported by the present study. These studies ensure comprehensive genetic analyses in several breeds to further compare parameters among breeds and identify interbreed differences in genetic variations of meat composition.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Mateescu et al. () reported heritabilities of anserine and carnosine in Angus cattle similar to those reported by the present study. These studies ensure comprehensive genetic analyses in several breeds to further compare parameters among breeds and identify interbreed differences in genetic variations of meat composition.…”
Section: Resultssupporting
confidence: 91%
“…Mateescu et al. () also reported a positive correlation between these peptides, although the magnitude was weaker. Positive and relatively large correlations would be beneficial for improvement of food functionality.…”
Section: Resultsmentioning
confidence: 88%
“…These data showed that the water buffalo meat contains more carnosine and less anserine, such as reported for beef and pork meats (Aristoy and Toldrà, 2004). In particular, all these values are lower than those reported for the l. dorsi beef muscle as previously reported (Mateescu et al, 2012;Toldrà and Reig, 2012), typically 372 and 66 mg/100 g of muscle for carnosine and anserine, respectively. Furthermore, the content of carnosine (average ~130.3 mg/100 g) and anserine (average ~17.9 mg/100 g) represents 50% of the total free amino acids, with a ratio of 7.3 fold higher for carnosine compared with anserine.…”
Section: Resultssupporting
confidence: 67%
“…The CRCs could be considered additional nutritional quality factors of meat . Previous studies have shown that the effects of CRCs on meat may vary depending on the animal species …”
Section: Resultsmentioning
confidence: 99%